2015
DOI: 10.3390/jmse3030772
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Site-Specific Kinetic Model for Chlorine Decay and the Formation of Chlorination By-Products in Seawater

Abstract: Chlorine is used commonly to prevent biofouling in cooling water systems. The addition of chlorine poses environmental risks in natural systems due to its tendency to form chlorination by-products (CBPs) when exposed to naturally-occurring organic matter (NOM). Some of these CBPs can pose toxic risks to aquatic and benthic species in the receiving waters. It is, therefore, important to study the fate of residual chlorine and CBPs to fully understand the potential impacts of chlorination to the environment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The rate of reaction with DOM is slower than the reaction with bromide and increases with increasing DOM concentrations (Wang et al 2008). Similar findings were obtained by Saeed et al (2015).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…The rate of reaction with DOM is slower than the reaction with bromide and increases with increasing DOM concentrations (Wang et al 2008). Similar findings were obtained by Saeed et al (2015).…”
Section: Introductionsupporting
confidence: 92%
“…Using CPO decomposition data and models from the literature (Wang et al 2008; Saeed et al 2015), a CPO concentration of 100 µg/L is predicted to decay to 50 µg/L within 2 h (~50%), and to 25 µg/L within 24 h (~75%) in a 5 to 15 °C receiving seawater environment. The CPO decomposition is slower at salinities lower than 35‰.…”
Section: Introductionmentioning
confidence: 99%
“…Similar trend was observed by Aravelo (2007) where results of his study showed that the rate of chlorine decay was found to be highly affected by the pipe material and the decay was faster in Steel pipe and slower in the synthetic pipes. Saeed et al (2015) carried out laboratory experiments to measure the changes in concentrations of residual chlorine with time under a variety of conditions. The study indicated tha the prominent factors that affect chlorine decay included initial chlorine dosage, temperature, pH and the amount of natural organic matter (NOM).…”
Section: Results and Discussion Scenariomentioning
confidence: 99%
“…Several investigators have reported the ecological fate of chlorine in water are understood, and it not remain in the environmental system for a long time (Truhlar et al 2006;Zheng et al, 2015;Cotton et al, 1999). Researchers have indicated that chlorine photolysis is naturally present in seawater through fate and transport of aerosols (Knipping and Dabdub, 2003;Saeed et al, 2015;Amy et al, 2017). When the chlorine gas reacts with water, it is immediately changed into different forms such as hypochlorous acid, chloride ion, and hypochlorite; however, hypochlorite is formed when pH falls below 4 (Farr et al, 2003).…”
Section: Chlorine Fate and Transport Into The Environmentmentioning
confidence: 99%